2014
DOI: 10.2527/jas.2013-6619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum on diarrhea and intestinal barrier function of young piglets challenged with enterotoxigenic Escherichia coli K881

Abstract: The present study was performed to investigate the preventative effect of Lactobacillus plantarum on diarrhea in relation to intestinal barrier function in young piglets challenged with enterotoxigenic Escherichia coli (ETEC) K88. Seventy-two male piglets (4 d old) were assigned to 2 diets (antibiotic-free basal diet with or without L. plantarum, 5 × 10(10) cfu/kg diet) and subsequently challenged or not with ETEC K88 (1 × 10(8) cfu per pig) on d 15 in a 2 × 2 factorial arrangement of treatments. Feed intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
121
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(137 citation statements)
references
References 28 publications
15
121
0
1
Order By: Relevance
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, the results indicated that piglets fed 5 Â 10 10 CFU L. acidophilus or 3000 mg ZnO/kg feed had greater ADG, lower F:G than the unsupplemetend group. Consistently, previous studies have established improved ADFI and ADG of piglets fed Lactobacillus strains (Lee et al 2012;Yang et al 2014;Qiao et al 2015) or ZnO (Hill et al 2001). Thus, we can speculate that both LA and ZnO could improve the growth and might partly attenuate the effects of the stress of piglets during the post-weaning period.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have shown that Lactobacillus strains (Lee et al 2012;Yang et al 2014) and ZnO (Hill et al 2001) were beneficial to growth performance and health status of weaning piglet. However, some studies indicated that L. brevis-supplementation feeding induced a nonsignificant increase in piglet body weight and caused no change in the morphology of the intestinal mucosa (L€ ahteinen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Segments of 2.0cm were sampled corresponding to duodenum (10cm from the pylorus), jejunum (the middle portion of the intestine) and the ileum (5cm from the ileo-caecal junction), according to YANG et al (2014). Samples were opened by the mesenteric border, extended by serous layer, washed in saline solution, fixed in Bouin solution for 24 hours, and sent to the Histology Laboratory of Veterinary Medicine Department of the Universidade Federal de Viçosa to prepare the slides.…”
Section: Methodsmentioning
confidence: 99%
“…The main symptoms are diarrhea, stunted growth, and high mortality. Diarrhea is a major challenge for neonatal and postweaning piglets, and results in a reduced growth rate, increased morbidity and mortality, and large economic losses in the global swine industry [1]. Nutritionists have devised a series of solutions such as adding antibiotics, probiotics, enzymes, and oligosaccharides to feed.…”
Section: Introductionmentioning
confidence: 99%